Best-fit heat stress metric for modelling the heat-mortality relation across climatically distinct subregions of Southern California - Caleb Schimke; Sandrah P. Eckel; Futu Chen; Hannah Schlaerth; Joseph Ko; Jaime Reyes-Sanchez; Dandan Wei; Sam J. Silva; Erika Garcia (Environmental Research, 2026)

Determinants of L-band backscatter in dry tropical ecosystems: Implications for biomass mapping - João M.B. Carreiras; Thomas Higginbottom; John L. Godlee; Sam Harrison; Lorena Benitez; Penelope J. Mograbi; Aurora Levesley; Karina Melgaço; David Milodowski; Georgia Pickavance; Geoff Wells; Edmar Almeida de Oliveira; et al. (Remote Sensing of Environment, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Small fish, big implications: considerations for an ecosystem approach to capelin fisheries management - Warsha Singh; John T. Trochta; Hannah M. Murphy; David W. McGowan; Aaron T. Adamack; Mayumi L. Arimitsu; Birkir Barðarson; Höskuldur Björnsson; Bjarte Bogstad; Mathieu Boudreau; Catherine Chambers; Harald Gjøsæter; et al. (Reviews in Fish Biology and Fisheries, 2025)

Drivers of carbon accumulation in eucalypt plantations: a multivariate analysis and prediction models for Australian and Brazilian experiments - Juliana Campos Amorim; João Marcos Rebessi de Sousa; Fábio Prataviera; Paulo Henrique Müller da Silva; Sérgio Augusto Rodrigues; Sam Van Holsbeeck; Saulo Philipe Sebastião Guerra; David J. Lee; Humberto de Jesus Eufrade-Junior (New Forests, 2025)

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Innovative curriculum strategies for managing the future of food science, technology and engineering education - I. Sam Saguy; Cristina L.M. Silva; Eli Cohen (Journal of Food Engineering, 2025)

Range-wide Distribution Survey, Habitat Modeling, and Characterization of Conservation Threats to the Colombian Black Spider Monkey (Ateles fusciceps rufiventris) in Colombia - Alma Hernández-Jaramillo; Sam Shanee; Juan Carlos Serio-Silva (International Journal of Primatology, 2025)

Predation on Live and Artificial Insect Prey Shows Different Global Latitudinal Patterns - Elena L. Zvereva; Benjamin Adroit; Tommi Andersson; Craig R. A. Barnett; Sofia Branco; Bastien Castagneyrol; Giancarlo Maria Chiarenza; Wesley Dáttilo; Ek del‐Val; Jan Filip; Jory Griffith; Anna L. Hargreaves; et al. (Global Ecology and Biogeography, 2024)
Aim Long‐standing theory predicts that the intensity of biotic interactions increases from high to low latitudes. Studies addressing geographic variation in predation on insect prey have often relied on prey models, which lack many characteristics of live prey. Our goals were to explore global latitudinal patterns of predator attack rates on standardised live insect prey and to compare the patterns in predation on live insects with those on plasticine prey models. Location Global forested areas. Time Period 2021–2023. Major Taxa Arthropods, birds. Methods We measured predation rates in 43 forested locations distributed across five continents from 34.1° S to 69.5° N latitude. At each location, we exposed 20 sets of three bait types, one set per tree. Each set included three live fly larvae (maggots), three live fly puparia and three plasticine models of the puparia. We used glue rings to isolate half of the sets from non‐flying predators. Results Arthropod attack rates on plasticine prey decreased linearly from low to high latitudes, whereas attack rates on maggots had a U shaped distribution, with the lowest predation rates at temperate latitudes and the highest rates at tropical and boreal latitudes. This difference emerged from intensive predator attacks on live maggots, but not on plasticine models, in boreal sites. Site‐specific attack rates of arthropod predators on live and plasticine prey were not correlated. In contrast, bird attack rates on live maggots and plasticine models were positively correlated, but did not show significant latitudinal changes. Main Conclusions Latitudinal patterns in predation differ between major groups of predators and between types of prey. Poleward decreases in both arthropod and combined arthropod and bird predation on plasticine models do not mirror patterns of predation on our live prey, the latter likely reflecting real patterns of predation risk better than do patterns of attack on artificial prey.

First report of Bemisia tabaci MEAM1 (Hemiptera: Aleyrodidae) resistance to spirotetramat in Florida - Marcelo Dimase; Bruno Rossito De Marchi; Sriyanka Lahiri; Julien Beuzelin; Sam Hutton; Felipe Barreto da Silva; Hugh A. Smith (Crop Protection, 2024)

A review of the application of hybrid machine learning models to improve rainfall prediction - Sam-Quarcoo Dotse; Isaac Larbi; Andrew Manoba Limantol; Liyanage C. De Silva (Modeling Earth Systems and Environment, 2024)

Ambient temperature and air pollution associations with suicide and homicide mortality in California: A statewide case-crossover study - Md Mostafijur Rahman; Melissa Lorenzo; George Ban-Weiss; Zainab Hasan; Mehjar Azzouz; Sandrah P. Eckel; David V. Conti; Fred Lurmann; Hannah Schlaerth; Jill Johnston; Joseph Ko; Lawrence Palinkas; et al. (Science of The Total Environment, 2023)

Probable signature whistle production in Atlantic white‐sided ( Lagenorhynchus acutus ) and short‐beaked common ( Delphinus delphis ) dolphins near Cape Cod, Massachusetts - Seth Cones; Molly Dent; Sam Walkes; Alessandro Bocconcelli; Christianna DeWind; Kayla Arjasbi; Kathryn Rose; Tammy Silva; Laela Sayigh (Marine Mammal Science, 2023)

Fine root dynamics across pantropical rainforest ecosystems - Walter Huaraca Huasco; Terhi Riutta; Cécile A. J. Girardin; Fernando Hancco Pacha; Beisit L. Puma Vilca; Sam Moore; Sami W. Rifai; Jhon del Aguila‐Pasquel; Alejandro Araujo Murakami; Renata Freitag; Alexandra C. Morel; Sheleme Demissie; et al. (Global Change Biology, 2021)
Fine roots constitute a significant component of the net primary productivity (NPP) of forest ecosystems but are much less studied than aboveground NPP. Comparisons across sites and regions are also hampered by inconsistent methodologies, especially in tropical areas. Here, we present a novel dataset of fine root biomass, productivity, residence time, and allocation in tropical old‐growth rainforest sites worldwide, measured using consistent methods, and examine how these variables are related to consistently determined soil and climatic characteristics. Our pantropical dataset spans intensive monitoring plots in lowland (wet, semi‐deciduous, and deciduous) and montane tropical forests in South America, Africa, and Southeast Asia ( n = 47). Large spatial variation in fine root dynamics was observed across montane and lowland forest types. In lowland forests, we found a strong positive linear relationship between fine root productivity and sand content, this relationship was even stronger when we considered the fractional allocation of total NPP to fine roots, demonstrating that understanding allocation adds explanatory power to understanding fine root productivity and total NPP. Fine root residence time was a function of multiple factors: soil sand content, soil pH, and maximum water deficit, with longest residence times in acidic, sandy, and water‐stressed soils. In tropical montane forests, on the other hand, a different set of relationships prevailed, highlighting the very different nature of montane and lowland forest biomes. Root productivity was a strong positive linear function of mean annual temperature, root residence time was a strong positive function of soil nitrogen content in montane forests, and lastly decreasing soil P content increased allocation of productivity to fine roots. In contrast to the lowlands, environmental conditions were a better predictor for fine root productivity than for fractional allocation of total NPP to fine roots, suggesting that root productivity is a particularly strong driver of NPP allocation in tropical mountain regions.

Major mutations in the NS3 gene region of hepatitis C virus related to the resistance to direct acting antiviral drugs: a systematic review - Ana Elisa de Figueiredo Miranda Mundim; Fernanda de Oliveira Feitosa de de Castro; Marina Brandão Braz Albuquerque; Cesar Augusto Sam Tiago Vilanova-Costa; Irmtraut Araci Hoffmann Pfrimer; Antonio Márcio Teodoro Cordeiro Silva (VirusDisease, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

SEASTAR: A Mission to Study Ocean Submesoscale Dynamics and Small-Scale Atmosphere-Ocean Processes in Coastal, Shelf and Polar Seas - Christine Gommenginger; Bertrand Chapron; Andy Hogg; Christian Buckingham; Baylor Fox-Kemper; Leif Eriksson; Francois Soulat; Clément Ubelmann; Francisco Ocampo-Torres; Bruno Buongiorno Nardelli; David Griffin; Paco Lopez-Dekker; et al. (Frontiers in Marine Science, 2019)

The role of wax and resin in the nestmate recognition system of a stingless bee, Tetragonisca angustula - Sam M. Jones; Jelle S. van Zweden; Christoph Grüter; Cristiano Menezes; Denise A. Alves; Patrícia Nunes-Silva; Tomer Czaczkes; Vera L. Imperatriz-Fonseca; Francis L. W. Ratnieks (Behavioral Ecology and Sociobiology, 2012)

Mutagenic and Genotoxic Effects of cis-(Dichloro)tetraammineruthenium(III) Chloride on Human Peripheral Blood Lymphocytes - Alessandra de Santana Braga Barbosa Ribeiro; Cláudio Carlos da Silva; Flávia de Castro Pereira; Aliny Pereira de Lima; Cesar Augusto Sam Tiago Vilanova-Costa; Simone Santos Aguiar; Luiz Alfredo Pavanin; Aparecido Divino da Cruz; Elisângela de Paula Silveira-Lacerda (Biological Trace Element Research, 2009)

Cytotoxic and Genotoxic Effects of cis-Tetraammine(oxalato)Ruthenium(III) Dithionate on the Root Meristem Cells of Allium cepa - Flávia de Castro Pereira; Cesar Augusto Sam Tiago Vilanova-Costa; Aliny Pereira de Lima; Alessandra de Santana Braga Barbosa Ribeiro; Hugo Delleon da Silva; Luiz Alfredo Pavanin; Elisângela de Paula Silveira-Lacerda (Biological Trace Element Research, 2009)